3D fracture modeling based on the coupling between damage criteria, phase field and crack propagation. Issue 1 (1st May 2022) - Bouchard, P-O; Eldahshan, H; Pino Munoz, D; Alves, J; Perchat, E
Abstract: In addition to predicting the onset of fracture, some specific material forming processes require the modeling of crack propagation and the accurate prediction of the fracture surface. In such configurations, the use of the deletion element technique is not adapted since it suffers from major mesh dependency and spurious artificial volume loss. This work introduces a new alternative in which the phase field method is coupled to a 3D automatic crack initiation and propagation technique within the Forge® finite element software.